2011
DOI: 10.1074/jbc.m111.225565
|View full text |Cite
|
Sign up to set email alerts
|

WW Domain-containing E3 Ubiquitin Protein Ligase 1 (WWP1) Delays Cellular Senescence by Promoting p27Kip1 Degradation in Human Diploid Fibroblasts

Abstract: WW domain-containing E3 ubiquitin protein ligase 1 (WWP1) plays an important role in the proliferation of tumor cells and the lifespan of Caenorhabditis elegans. However, the role of WWP1 in cellular senescence is still unknown. Here, we show that the expression patterns of p27 Kip1 and WWP1 are inversely correlated during cellular senescence. Moreover, the overexpression of WWP1 delayed senescence, whereas the knockdown of WWP1 led to premature senescence in human fibroblasts. Furthermore, we demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…It is possible that the induction of WWP1 by TGFb is a negative feedback mechanism for controlling the TGFb signaling pathway since WWP1 suppresses TGFb signaling [1,22]. During the cellular senescence, WWP1 has been shown to be downregulated [30].…”
Section: Regulation Of Wwp1mentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that the induction of WWP1 by TGFb is a negative feedback mechanism for controlling the TGFb signaling pathway since WWP1 suppresses TGFb signaling [1,22]. During the cellular senescence, WWP1 has been shown to be downregulated [30].…”
Section: Regulation Of Wwp1mentioning
confidence: 99%
“…In addition, WWP1 overexpression promoted breast epithelial cell growth and anchorageindependent growth [24]. In 2BS and WI38 fibroblast cell lines, overexpression of WWP1 increased cell proliferation while depletion of WWP1 induced senescence [30]. WWP1 enhances cell proliferation and survival likely through both ubiquitin ligase-dependent and -independent activities.…”
Section: Wwp1 and Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In intravital imaging in kidneys of HFD-fed wild-type mice using two-photon laser scanning microscopy, abnormal autofluorescence was found in PTECs ( Figure 2C) that were located in the S2 segment ( Supplemental Figure 3). The intracellular distribution and tubular localization patterns of the autofluorescent substances indicated that they were contained in dysfunctional autolysosomes of PTECs.…”
Section: Vacuolized Ptecs In Hfd-fed Mice Show Evidence For Lipid Permentioning
confidence: 99%
“…WWP1 harbors three various domains, including four tandem WW domains, an N-terminal C2 domain, and a homologous E6AP carboxy terminus (HECT) region [13,14], which encodes 922 amino acid residues with the molecular weight of 110 kDa [15]. Accumulating evidence has showed that WWP1 is implicated in the regulation of a variety of biological processes, such as protein trafficking and degradation, signaling transduction, cellular senescence, transcription, and viral budding [15][16][17][18]. Currently, more and more studies have revealed that WWP1 plays pivotal roles in the occurrence, development, progression, and prognosis of many tumors including hepatocellular carcinoma [19], oral cancer [20], breast carcinoma [9], and prostate cancer [4].…”
Section: Introductionmentioning
confidence: 99%